2006
DOI: 10.1021/ja056358i
|View full text |Cite
|
Sign up to set email alerts
|

PNA-Based Reagents for the Direct and Site-Specific Synthesis of Thymine Dimer Lesions in Genomic DNA

Abstract: An acetophenone containing PNA-based reagent was designed for the direct and site-specific synthesis of a cis-syn thymidine dimer lesion in genomic DNA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…The obtained compounds were then alkylated with 4-(bromomethyl)acetophenone, which was prepared by radical bromination of 4-methylacetophenone ( not described ). [12] The alkylated derivatives 11a-m were isolated in moderate yields (31–56%) after 24 h at room temperature. Finally, the methyl ketone intermediates were treated with LiHMDS and reacted with diethyl oxalate to produce the α,γ –diketoesters derivatives, which were subsequently submitted to base-promoted hydrolysis (saponification) and acidification to yield the desired α,γ-diketobutanoic acids 4a-m in good yields, over two steps.…”
Section: Resultsmentioning
confidence: 99%
“…The obtained compounds were then alkylated with 4-(bromomethyl)acetophenone, which was prepared by radical bromination of 4-methylacetophenone ( not described ). [12] The alkylated derivatives 11a-m were isolated in moderate yields (31–56%) after 24 h at room temperature. Finally, the methyl ketone intermediates were treated with LiHMDS and reacted with diethyl oxalate to produce the α,γ –diketoesters derivatives, which were subsequently submitted to base-promoted hydrolysis (saponification) and acidification to yield the desired α,γ-diketobutanoic acids 4a-m in good yields, over two steps.…”
Section: Resultsmentioning
confidence: 99%
“…After photon absorption, the excited FADH − in photolyase protein transfers an electron to the pyrimidine dimer lesion in the duplex DNA . As a model system, Carell et al reported a photoinduced DNA-repair reaction from a flavin donor to a thymine dimer acceptor introduced in an oligonucleotide or a defined DNA scaffold as photolyase mimics . In addition, another type of cofactor, redox-active [4Fe4S] cluster, is also found in DNA repair proteins. , Barton et al demonstrated DNA-mediated ET between the [4Fe4S] cluster in two of these proteins, MutY and endonuclease III, and the guanine radicals .…”
Section: Introductionmentioning
confidence: 99%
“…-(Bromomethyl)acetophenone 1 was obtained as a white solid according to the published procedure[53]. Yield: 15.1 g (95%).…”
mentioning
confidence: 99%